1990
DOI: 10.1213/00000539-199001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Electrocardiographic Changes During Cesarean Delivery Under Regional Anesthesia

Abstract: Serial electrocardiograms were obtained on 93 healthy ASA physical status I and II term parturients during nonemergent cesarean delivery under regional anesthesia. Electrocardiographic changes occurred in 44 of the 93 patients (47.3%); in 35 of these 44 patients, the changes were characteristic, or suggestive, of myocardial ischemia. Symptoms of chest pain, pressure, and dyspnea occurred in 15 of the 44 patients with electrocardiographic changes; no patient without electrocardiographic change developed symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 14 publications
3
44
1
1
Order By: Relevance
“…11,26 The total incidence rate of ST depressions in the present study is comparable with previous reports, but studies are generally difficult to compare as there is variety in the numbers of subjects included, anaesthetic methods as well as different doses and administration routines regarding oxytocin. [1][2][3] In previous studies, most of the ST depressions have occurred after delivery, which is the time period, when oxytocics are given. 1,2,4 Oxytocin as a causative agent has not been discussed in detail in previous studies and is sometimes not mentioned at all.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,26 The total incidence rate of ST depressions in the present study is comparable with previous reports, but studies are generally difficult to compare as there is variety in the numbers of subjects included, anaesthetic methods as well as different doses and administration routines regarding oxytocin. [1][2][3] In previous studies, most of the ST depressions have occurred after delivery, which is the time period, when oxytocics are given. 1,2,4 Oxytocin as a causative agent has not been discussed in detail in previous studies and is sometimes not mentioned at all.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In previous studies, most of the ST depressions have occurred after delivery, which is the time period, when oxytocics are given. 1,2,4 Oxytocin as a causative agent has not been discussed in detail in previous studies and is sometimes not mentioned at all. 2,3 The association between ST depression and oxytocin administration is in agreement with the results by Svanstrom et al, 5 who in a double blind, randomised controlled trial studied effects of oxytocin bolus on ECG in comparison with methylergometrine, in patients undergoing elective CS under spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These complaints are similar to those made by symptomatic cardiac patients with myocardial ischaemia. Palmer et al 1 found that ECG changes occurred in 47% of parturients. In fact, these investigators speculated that myocardial ischaemia was the likely cause of both the ECG changes and the chest pain that develops in these patients.…”
Section: Cardiac Enzymes In Patients Undergoingmentioning
confidence: 99%